Analisis Program Rehabilitasi Narkotika dan Dampaknya terhadap Peningkatan Kualitas Hidup Pengguna Narkoba - Salsabila Putri Zahra Nasution; Boedi Prasetyo (Jurnal Hukum Lex Generalis, 2024)
This study focused to analyze the effectiveness of drug rehabilitation programs and their impact on improving the quality of life of users. Drug rehabilitation in Indonesia has become an important part of efforts to overcome drug abuse, but the effectiveness of this program is still debated. The research method used is a case study with a qualitative approach, collecting data through in-depth interviews with rehabilitation participants, rehabilitation officers, and document analysis related to the rehabilitation program. The results of the study indicate that the drug rehabilitation program has a positive impact on the quality of life of users in several aspects, including physical and mental health, social relationships, and the ability to adapt to the environment. Factors that influence the success of rehabilitation include family support, involvement in group therapy, and the sustainability of the post-rehabilitation program. However, challenges faced include the lack of adequate facilities, limited human resources, and social stigma against former drug users. This study also identifies the importance of a more holistic and sustainable rehabilitation approach, including an emphasis on life skills development, psychosocial support, and economic recovery for former users. These findings are expected to provide insight for policy makers and practitioners in designing more effective drug rehabilitation programs that can improve the quality of life of drug users as a whole.